Neighborhood Association (RT)-Based Training Education on Hydroponic Melon Cultivation for Communities Without Experience in Modern Agriculture - Bambang Agus Sumantri; Sekar Widyasari Putri; Muhammad Dwi Hariyanto; Titus kristanto; Titus kristanto; Agoes Windarto (Abdi Masyarakat, 2026)
This community service training not only introduces hydroponic technology for melons as an alternative agricultural solution, but also raises public awareness of the importance of sustainable use of local resources. By involving the community in every stage—from outreach to cultivation practices—it is hoped that independence in managing productive small-scale agricultural businesses will grow. This could be the starting point for the birth of hydroponic farmer groups or community-based agricultural entrepreneurs at the neighborhood level. The participants, consisting of 10 residents of neighborhood associations (RT) 01 and neighborhood associations (RW) 03, are expected to be able to improve local food security and family income.